Peningkatan Hasil Panjualan Melalui Pemanfaatan “Digital Marketing dan Komputer Masyarakat” Bagi Masyarakat - Tajuddin Abdillah; Roviana H. Dai; Lillyan Hadjaratie (Univeristas Negeri Gorontalo, 2019)
Priority issues of partners according to mutual agreement to be resolved during the implementation of the independent village - campus project program are: (1) Determining the base price and selling price; (2) The recording of the results of sales / orders by consumers / buyers is still done; (3) The sales / marketing process still relies on a direct sales system and has not yet served requests from outside the region. The solution is: partners will be given a website, and website hosting for free by implementing partners will be given training on financial management. The output is: partner sales have increased, because they can serve purchases online. The goal to be achieved in implementing the project program activities in independent villages is to increase production and partner income through the use of information technology-based applications. The methods that will be used in achieving these goals are training and mentoring (lectures and practices) as well as evaluation of the achievement of targets for the implementation of project program activities in independent villages.